A global synthesis of reported urban tree carbon production rates and approaches - Jenerette, G. Darrel; Herrmann, Dustin L. (Frontiers in Ecology and Evolution, 2024)
Trees are a prominent feature of urban ecosystems. Urban tree productivity is a key component of urban ecosystem energetics and has been identified as a possible pathway for reducing global greenhouse gas concentrations. Recently, extensive research has been directed to evaluating the carbon dynamics of urban trees in cities throughout the world. Here we synthesize this research, using results from previous studies from 154 cities to identify the distribution of urban tree productivity globally and the basis for generating urban tree productivity estimates. Reported urban tree productivity shows a strong relationship with estimated tree carbon content and exhibits increases with both temperature and precipitation, with land cover differences influencing the degree of climate sensitivity. Compared to a reference productivity estimate, urban trees showed greatly reduced estimated rates of productivity and the magnitude of reduced productivity was inversely correlated with precipitation but was independent of temperature.Reported rates of productivity across all studies suggest climate restrictions that are more important with less intensively managed land covers. Scaling these results globally suggests a limited opportunity for urban trees to contribute to atmospheric carbon dioxide reductions, especially in the absence of major carbon emission reductions. We found the majority of results are derived from tree inventories from a single period with rates of productivity estimate through quasi-empirical or allometric models. The majority of studies have been conducted in temperate biomes and North America. These results show that existing urban tree assessments have substantial methodological restrictions and regional biases. Future research of urban tree productivity should look toward improved methods and can use this synthesis as a baseline for comparisons and improvement.